Determination of reference intervals and decision limits for thyroid stimulating hormone and thyroxine on cord blood samples - Mahomed, Mariam (Department of Pathology, 2025)
Background: Congenital hypothyroidism (CH) is a significant health concern globally, with severe consequences if left untreated. Newborn screening (NBS) programs play a pivotal role in early detection and intervention of CH. However, due to resource constraints, South Africa lacks a national NBS program. This study aimed to establish reference intervals for thyroid stimulating hormone (TSH) and free thyroxine (FT4) in cord blood, as well as to compare the previous TSH radioimmunoassay with the current electrochemiluminescence immunoassay. Methods: Utilizing residual samples from the Peninsula Maternal and Neonatal Services (PMNS) CH Screening Program, this prospective study collected samples from uncomplicated pregnancies, resulting in 121 samples for reference interval analysis. Additionally, 14 samples within pathological ranges were selected, bringing the total for the method comparison study to 135. TSH and FT4 levels were determined by automated immunoassay on the Roche Cobas® 6000 analyser (Elecsys TSH and Elecsys FT4 III assays). The data analysis was performed following relevant CLSI guidelines (CLSI EP28-A3c and CLSI EP09-A3). Results: In the reference interval study, the mean birth weight was 3,211g (+/-387g). Non-parametric methodology yielded a TSH reference interval of 1.85 to 15.35 mIU/L and a free T4 reference interval of 13.0 to 20.4 pmol/L. The TSH method comparison study demonstrated strong agreement between the radioimmunoassay and electrochemiluminescence immunoassay (R-squared=0.98; Lin's CCC=0.97). Bland-Altman analysis revealed most points within the European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) total allowable error goals for TSH, with RIA results showing a small positive bias. Conclusion: This study establishes reference intervals for cord blood TSH and FT4 in a South African context. Cord blood presents advantages for CH screening in resource-constrained settings, integrating with existing labour and delivery protocols while minimizing logistical challenges. The established intervals align with existing literature and methodologies, supporting their validity and applicability. Continued monitoring of the CH program and clinical outcomes is crucial for validating the study results in a clinical context, ensuring ongoing relevance and accuracy.